ANALISIS PENGELOLAAN PIUTANG SEBAGAI UPAYA MENINGKATKAN PROFITABILITAS PADA KOPERASI UNIT DESA “KARYA SEMBADA” DI DESA BATANG BATINDIH KECAMATAN RUMBIO JAYA KABUPATEN KAMPAR - Marwati "; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the level of receivables turnover that occurs on profitability at the Karya Sembada Village Unit Cooperative for the 2016-2020 period based on the annual financial report consisting of the balance sheet and the remaining operating results of the Cooperative. This type of research is quantitative descriptive, with the type of data used by the researcher is quantitative data which is statistics in the form of numbers. Sources of data used are primary data sources in the form of interviews and secondary data sources in the form of annual financial reports of cooperatives. Based on the results of the analysis of receivable management as an effort to increase profitability at KUD Karya Sembada, Batang Batindih Village, Rumbio Jaya District, Kampar Regency, it was concluded that: 1) The Receivable Turn Over of Karya Sembada KUD from 2016-2020 was in the Bad category. 2) The level of profitability in 2016-2020 in terms of ROA is in the Bad category, ROE is in the Fairly Good category, and NPM is in the Very Good category. 3) The level of receivable management as an effort to increase profitability in cooperatives is in the Bad category in managing receivables turnover to maximize its income. Keywords: Accounts Receivable Turnover, Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM)